Surgical Complications in 1408 Primary Cleft Palate Repairs Operated at a Single Center in Guwahati, Assam, India. (May 2016) - Schönmeyr, Björn; Wendby, Lisa; Campbell, Alex
Objective: To analyze surgical complications after primary cleft palate repair in a setting with limited resources. Patients and Design: A total of 1608 consecutive cleft palate repairs with 1408 follow-ups, operated upon between 2011 and 2013, were reviewed retrospectively through medical records. Patients were 10 months to 50 years old at the time of surgery, with a median age of 9 years. Setting: Guwahati Comprehensive Cleft Care Center, Guwahati, India. Intervention: Primary cleft palate repair. Main Outcome Measures: Postoperative complications in terms of necrosis, dehiscence, fistula, infection, and "hanging palate" were assessed, as was perioperative bleeding. Logistic regression was used with complication (yes/no) as the binary dependent variable and with age, cleft type, and surgeon (visiting/long-term) as covariates. Results: The overall incidence of postoperative complications was 16.9% with a fistula rate of 13.6%. The incidence of perioperative bleeding was 1.8%. Logistic regression analysis identified cleft severity ( P ≤ .001) and visiting surgeon ( P ≤ .01) as factors related to the incidence of postoperative complications. Age at surgery was related to both the incidence of postoperative complications ( P ≤ .001) and perioperative bleeding ( P < .05). Conclusion: Due to increased risks of surgical complications, older patients with complete clefts should only be operated upon after careful consideration. In addition, these patients should be assigned to surgeons experienced with this cleft type.